(untitled) (Journal of Bio-Science, 2016)
Nutrient use efficiency determines precisely a certain amount of plant yield in terms of grains or biomass per unit of applied nutrients. Crop plants contain many more elements but for their growth and development basically they require almost sixteen mineral nutrients, among which N, P, K are used in large amount and N covers manifold function for contribution of the yield attributes. In deficiency of any micro- or macro-nutrient and due to few environmental factors plant growth along with its yield are affected adversely. In addition to physiological and breeding strategies genetic progress and implications have characterized this area to some extent. As nutrient efficiency is expressed in several ways, this phenomenon is taken in a wrong sense among the concerned persons and thus, there should be a balance between optimum nutrient use efficiency and optimum crop productivity based on the selected phenotypic characters of crop plants. Nutrient use efficiency is said to be a complex trait. Even its different stages of action are also considered complicated in nature. In such case a single gene can provide huge benefit. This is why modern genetic tools and resources available to the scientists have provided a great possibility for increasing nutrient use efficiency in crop plants. Molecular biology offers possibility for improving the desired characters by introduction of the specific gene(s). Augmentation of nutrient content of crop plants is being caused through genetic engineering. This article makes review and discussion on the genetic approaches in terms of exploited genetic engineering and biotechnological tools for increasing the specific nutrients especially nitrogen in cereal crops. J. bio-sci. 22: 111-125, 2014